The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3945/ajcn.110.001305
|View full text |Cite
|
Sign up to set email alerts
|

Dietary factors and incident atrial fibrillation: the Framingham Heart Study

Abstract: Consumption of alcohol, caffeine, fiber, and fish-derived PUFAs was not significantly associated with AF risk. The observed adverse association between the consumption of dark fish and AF merits further investigation. Our findings suggest that the dietary exposures examined convey limited attributable risk of AF in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 47 publications
4
96
3
Order By: Relevance
“…We did not separately assess risk of AF according to physical activity intensity, and these differences can not be excluded in this cohort as well. Similar to our study, prior literature has not demonstrated a reliable association between either total cholesterol or dietary components and AF 36, 37, 38, 39, 40, 41, 42. No previous studies have explored whether specific dietary patterns might be associated with the risk of AF.…”
Section: Discussionsupporting
confidence: 86%
“…We did not separately assess risk of AF according to physical activity intensity, and these differences can not be excluded in this cohort as well. Similar to our study, prior literature has not demonstrated a reliable association between either total cholesterol or dietary components and AF 36, 37, 38, 39, 40, 41, 42. No previous studies have explored whether specific dietary patterns might be associated with the risk of AF.…”
Section: Discussionsupporting
confidence: 86%
“…Previous epidemiological assessments of dietary exposures in relation to AF have obtained inconsistent results. [23][24][25] A potential protective effect of long chain omega-3 fatty acids from fish, especially docosahexaenoic acid, has been suggested in some 26,27 but not all [23][24][25]28,29 studies. To the best of our knowledge, there are no data from observational epidemiological studies to support or refute an association between EVOO consumption and reduced AF risk.…”
Section: Discussionmentioning
confidence: 99%
“…The method of caffeine exposure ascertainment was unclear in the study performed by Wilhelmsen et al [15]. Two studies were conducted in the USA [16,17] and 6 in Europe (4 in Sweden [10,13,15], 1 in Denmark [18], and 1 in Italy [14]). The lengths of the 7 cohort studies were considered to be reasonable, with a mean follow-up ranging from 4 to 25 years.…”
Section: Description Of Studiesmentioning
confidence: 99%